Odor-active volatile compounds in preterm breastmilk - Laura Galante (Pediatric Research, 2022)
Background: Volatile compounds in breastmilk (BM) likely influence flavor learning and, through the cephalic phase response, metabolism, and digestion. Little is known about the volatile compounds present in preterm BM. We investigated whether maternal or infant characteristics are associated with the profile of volatile compounds in preterm BM. Methods: Using solid-phase microextraction coupled with gas chromatography/mass spectrometry, we analyzed volatile compounds in 400 BM samples collected from 170 mothers of preterm infants. Results: Forty volatile compounds were detected, mostly fatty acids and their esters (FA and FAe), volatile organic compounds (VOCs), aldehydes, terpenoids, alcohols, and ketones. The relative concentration of most FA and FAe increased with advancing lactation and were lower in BM of most socially deprived mothers and those with gestational diabetes (p < 0.05), but medium-chain FAs were higher in colostrum compared to transitional BM (p < 0.001). Infant sex, gestational age, and size at birth were not associated with the profile of volatile compounds in preterm BM. Conclusions: Sensory-active volatile FA and FAe are the major contributors to the smell of preterm BM. The associations between lactation stage, maternal characteristics, and volatile compounds, and whether differences in volatile compounds may affect feeding behavior or metabolism, requires further research.